Optimization of Processing and Packaging Technology to Improve the Quality of Fish Products Caught by Local Fishermen in the Coastal Area of Bima Bay - Amran, Amran; Riandi, M. Inas (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to optimize processing and packaging technologies to improve the quality of fish products caught by local fishermen in Bima Bay. The methods included a survey of 50 fishermen, processing experiments (blanching, quick freezing, vacuum packaging), and microbiological, sensory, and community acceptance tests. The results showed that the dominant fish species were skipjack (35%), tuna (30%), and scad (20%). Processing with blanching and quick freezing reduced microbial growth by up to 90% compared to untreated samples. Sensory evaluation indicated an 85% acceptance rate for vacuum-packed frozen fish. Community surveys revealed that 80% of fishermen were willing to adopt this technology. These findings demonstrate that appropriate technology based on quick freezing and vacuum packaging can improve fish quality, reduce post-harvest losses, and contribute to fishermen’s welfare.